Effect of intracanal cryotherapy on post-operative pain in single-visit endodontic retreatment: a randomized clinical trial - Sholeh Ghabraei; Farzaneh Afkhami; Mohammad Mahdi Kiafar; Mohamad Javad Kharazifard; Ove A. Peters (BMC Oral Health)
Abstract Background This randomized clinical trial aimed to evaluate the effect of intracanal cryotherapy with 2–4 °C normal saline irrigation on post-operative pain after single-visit non-surgical root canal retreatment. Methods Forty-six single-rooted, single-canal teeth requiring non-surgical root canal retreatment were randomly assigned to two groups (n = 23): a cryotherapy group and a control group. All the treatments were completed during a single visit. A combination of nickel-titanium and stainless-steel files was used for the removal of gutta-percha and root canal preparation, and irrigation was performed using 5.25% NaOCl and 17% EDTA. The cryotherapy group had a final irrigation temperature of 2–4 °C for 5 min before root canal obturation, whereas the control group received irrigation at room temperature. Post-operative pain levels were assessed via the Numerical Rating Scale at 6, 18, 24, 48, 72, and 168 h (up to 7 days). The number of analgesics consumed at the same intervals was also recorded. Statistical analysis was performed using the Chi-Square test, Mann-Whitney test, and Independent Samples test, with the significance level set at 0.05. Results There was a statistically significant difference in post-operative pain between the cryotherapy group and the control group at 6 h after treatment (P < 0.05). However, post-operative pain levels were not significantly different at 18, 24, 48, 72, or 168 h after treatment (P > 0.05). Additionally, there was no statistically significant difference between the groups in terms of analgesic intake (P > 0.05). Conclusion Intracanal cryotherapy can effectively reduce short-term post-operative pain, but it has no effect on long-term pain or the need for analgesics.